La literatura de la Cristiada: una visión apocalíptica de la historia de México (Altre Modernità, 2013)
The collapse of social and political order provoked by the 1910 Mexican Revolution and the Cristero war (1926-1934) are two historical moments that saw the breakdown of the religious world’s certainty. Apart from the institutional conflict between Catholic church and Mexican State, the people experienced the threat of a hecatomb, the deprivation of religious protection, known and alive since the period of the Spanish conquest and colonization. This lack of a space for the community and the impossibility of expressing religious rites fed an apocalyptic vision of the world.Not being allowed to access places of worship under the government of Plutarco Elías Calles unleashed the violent reaction of a profoundly religious people, which took arms to defend what it considered fundamental: its own ancestral tradition and a sacred space which it had been denied.In the midst of the silences which official historiography maintained during the years following this unpleasant chapter of Mexican history, Cristero literature has constructed its own vision, an apocalyptic vision which breaks down the temporal and social boundaries within which it has been studied. The present work concentrates on the analysis of the Cristero novel which represents the Cristiada from different perspectives, one of which underlines the redeeming nature of the battle favoring the use of the apocalyptic metaphor of martyrdom.